THE INFLUENCE OF PRE-SOWING SEED TREATMENT ON THE FORMATION OF THE PRODUCTIVITY OF ALFALFA SOWING - Марініч, Любов; Климась, Едуард (SWorldJournal, 2023)
Topicality. To increase the production of quality fodder, the improvement of the structure of sown areas and the organization of cultural pastures become important. In this case, it is the effective use of perennial leguminous grasses that can establish a